Implementation of Auditing in Zakat Institutions: Case studies of BAZNAS Riau and Pekanbaru - Devi Megawati (Tazkia Islamic Finance and Business Review, 2018)
This paper examines the implementation of auditing in Zakat Institutions with a case study in BAZNAS Riau Province and BAZNAS Pekanbaru. Nowadays, the government and citizen’s attention for zakat management has become so high. Therefore, there are publications of rules about the obligation of zakat Institutions to make the report which, then, is an object to be audited. The researcher interviewed some regarding this topic, such as the Commisioner Head and Manager of BAZNAS Riau province and BAZNAS Pekanbaru and some staff of the Ministry of Religion who are in charge of zakat. The findings show the high attention of important role of internal auditor in zakat institutions. In the case at BAZNAS Pekanbaru, a team of internal auditors has been formed in 2017. The internal auditing activities can be the starting point for the external auditing activity. External auditing in zakat institutions industry facing many challenges such as waiting the release of technical rules of sharia audit from Ministry of Religious Affairs. The paper contributes to the better governance for zakat institutions to increase the trust of moslems especially muzakki in Riau province.